Speak, move, play and learn with children on the autism spectrum : activities to boost communication skills, sensory integration and coordination using simple ideas from speech and language pathology and occupational therapy /: activities to boost communication skills, sensory integration and coordination using simple ideas from speech and language pathology and occupational therapy. (©2012) - Unknown
No abstract available